The changing dynamics of integrated international sourcing, production and marketing networks : theory and evidence. - Koh, Wee Ying. (2008)
This study investigates, through the formulation of a conceptual framework, the interaction of two fundamental components – relationships and complexities – of the supply chain. It discusses how firms may move in different directions on the model and the resulting implications, and further analyses the conundrums faced by firms in globalised markets.